DECISION TO USE ISLAMIC BANKS DURING ECONOMIC UNCERTAINTY. DOES PERCEIVED SECURITY MODERATE THE PROCESS? - Rachman, Fariza; Abdul Ghani Azmi, Ilhaamie; Oetomo, Hening Widi (Online Journal of Islamic Management and Finance (OJIMF), 2023)
This paper aims to examine the effect of Islamic marketing mix implementation and the moderating role of perceived security towards Islamic bank customers' decisions in the context of economic uncertainty, by taking place at Surabaya, Indonesia. A strong connection between Islamic bank achievement and economic adversity has been affirmed by multifarious research, however; the perceived security among recent IB customers is less discussed. Measuring the influence of Islamic bank marketing mix implementation towards its customers’ decision making combined with perceived security as the moderating variable is somewhat not as sound as it should be. This is the gap that the researchers want to fill. This paper utilizes Structural Equation Modelling (SEM) and Moderating Regression Analysis (MRA) as the analysis technique, along with Confirmatory Factor Analysis (CFA). The significancy test shows that the perceived security does not present any moderating effect, yet, it acted as the second significant independent variable together with the IB’s Islamic marketing mix, towards the decision-making. Put simply, it means that the respondents deliberately sought security from Islamic banks to confront, or anticipate economic uncertainty.